Mutation-Based Testing of Integer Overflow Vulnerabilities - Fanping Zeng; Liangliang Mao; Zhide Chen; Qing Cao (2009 5th International Conference on Wireless Communications, Networking and Mobile Computing, 2009)
Integer overflow vulnerability is a kind of common software vulnerabilities, there has been no effective way to detect integer overflow vulnerabilities. Because of the lack of dynamic execution, static analysis can not determine the run-time distribution of memory, and may miss the detection of possible security issues; source code auditing is an expensive and time consuming process. Although there has been applying mutation analysis for testing ANSI C programs, and lots of mutation operators have been designed with respect to specific questions, there are not any of operators specifically designed for integer overflow. In this paper, we propose some new mutation operators to force the generation of adequate test data set for integer overflow vulnerabilities. The results indicate that the proposed operators are effective for detecting integer overflow vulnerabilities.